Analysis of the Effect of Attitudes and Good Behavior on Character Building (Literature Review Study) - Saputra, Raihan (Green Publisher, 2022)
Literature Review Article Analysis of the Effect of Good Attitudes and Behavior on Character Building (Study Literature Review) is a scientific article that aims to build a research hypothesis on the influence of variables that will be used in further research. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Attitude affects Character Building; and 2) Good Behavior affects Character Building. Apart from these 2 exogenous variables that affect the endogenous variable Character Building, there are still many other factors including the variables of Student Ability, Student Interest and Student Understanding.